Cognitive functioning following traumatic brain injury: A five-year follow-up - Marsh, Nigel V.*; Ludbrook, Maria R; Gaffaney, Lauren C (IOS Press, 2016)
To describe the long-term prevalence and severity of cognitive deﬁcits following signiﬁcant (i.e., ventilation required for >24 hours) traumatic brain injury. To assess a comprehensive range of cognitive functions using psychometric measures with established normative, reliability, and validity data. A group of 71adults was assessed at approximately ﬁve years(mean=66months)following injury. Assessment of cognitive functioning covered the domains of intelligence, attention, verbal and visual memory, visual-spatial construction, and executive functions. Impairment was evident across all domains but prevalence varied both within and between domains. Across aspects of intelligence clinical impairment ranged from 8–25%, attention 39–62%, verbal memory 16–46%, visual memory 23–51%,visual-spatialconstruction38%,andexecutivefunctions(verbalﬂuency)13%.Inaddition,3–23%ofperformances across the measures were in the borderline range, suggesting a high prevalence of subclinical deﬁcit. Although the prevalence of impairment may vary across cognitive domains, long-term follow-up documented deﬁcits in all six domains. These ﬁndings provide further evidence that while improvement of cognitive functioning following signiﬁcant traumatic brain injury may be possible, recovery of function is unlikely.